Transisi Budaya di Bali dalam Novel Jerman: Wayan zwischen Drogen und D monen - Kurnia, Lilawati (UI Scholars Hub, 2006)
Europe has been interested in Indonesia for many centuries ago. The Dutch Government and the East-Indies Company (VOC), for example, already established the connection between Indonesian and German along with the colonization when the VOC brought the German Regiment to the islands of Indonesia. Nevertheless, this relationship was not in a friendly way but was the power one. German also adopted the domination of the colony by the Dutch. Bali as the foremost attraction for the Europe since the 19th century has become a place of destination to the western tourists in the 20th century. The transition of Balinese culture and people can be seen in every aspect. The novel Wayan zwischen Drogen und D monen shows how the Balinese in mid 20th century is influenced by the western culture and how they survive during the transition from tradition to modernity.